Description on 10th grade–science Students’ Problem solving skill based on Wankat and Oreovics Theory viewed from Mathematical logical intelligence - Nurul Masynaeni; Djadir; Rusli (ARRUS Journal of Mathematics and Applied Science, 2021)
This research aims to describe the ability of problem-solving based on the theory of Wankat and Oreovicz reviewed from mathematical logical intelligence in a system of linear equations in three variables. This research is a qualitative research with a descriptive method. The subjects in this research were students of class X IPA who represent each category of mathematical logical intelligence that is high, medium, and low. The research instruments consist of the mathematical logical intelligence test, the problem-solving ability test, and the interview guidelines. The results of research show that: (1) the student with high mathematical logical intelligence was able to solved the problem well. (2) the student with medium mathematical logical intelligence was able to do problem solving altough they did exprience misconseption in the calculating process; (3) the student with low mathematical logical intelligence was able to carry out same step of problem solving that is exploration step.